LEARNING OBJECTIVE OF THE ANATOMY CIRCULATION SYSTEM FOR THE MEDICAL STUDENTS: A DELPHI STUDY - Marwatunnisa Al Mubarokah; Siti Munawaroh; Yunia Hastami; Nanang Wiyono (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2020)
Background: Anatomy is basic science that is important for preclinical students, clinics, and specialists. The development of medical science led to a reduced allocation of learning time in Anatomy. The imbalance between the amount of learning material with time allocation makes various effective teaching methods carried out and examined. The learning objectives guide the faculty in selecting teaching methods as well as appropriate evaluation to measure the progress of student understanding. This study aims to obtain detailed anatomical learning objectives regarding the circulation system for medical students as part of the development of the medical curriculum in Indonesia.Method: This research is qualitative research with the modified Delphi method. The research subjects were anatomy lecturers in Indonesia who. The first round of the Delphi questionnaire was filled out by selecting the Bloom cognition domain between C1-C6 and the respondent composing the sentence of learning objectives according to the core material. The second round of respondents was asked to choose an important level from each point of learning objectives on the Likert Scale 1-4. The consensus level chosen is that 60% of the panel chooses on level 3 or 4.The results of the second round are then processed to ensure the most appropriate selection of operational verbs and cognitive domains.Results: The first Delphi round resulted in 74 learning objectives from 110 core material points with the cognitive domain between C1-C3. While the second round, Delphi generates 59 learning objectives. The third round which was not part of the Delphi method, these results were then consulted to anatomists of the circulatory system and came up with the 32 learning objectives.Conclusion: The learning objectives of the circulation system that need to be known are 32 learning objectives, with cognitive domains varying between C1-C3, include cor, pericardium, mediastinum, arteries, veins, lymphatics system, prenatal and postnatal circulation, dan hepatic portal  system. Keywords: anatomy of circulatory system, Delphi method, anatomy learning objectives, lecturer consensus